Formulation of liposomes loading lentisk oil to ameliorate topical delivery, attenuate oxidative stress damage and improve cell migration in scratch assay - Mohamad Allaw (Elsevier, 2021)
Pistacia lentiscus L. is a sclerophyllous shrub capable of growing under harsh climatic conditions especially in the Mediterranean Basin. Different products can be obtained from this plant, such as essential oil, mastic gum or even fixed oil. The last is well known for its flavor which is mainly exploited in the food industry. Additionally, it has been traditionally used in the treatment of skin diseases, but, at the moment, any suitable formulation for skin delivery has been formulated and its biological effects was not deeply confirmed. Given that, in the present study, the lentisk oil has been formulated in liposomes at different concentrations (10, 20, 30 mg/ml) and their physicochemical, technological and main biological properties have been evaluated. Vesicles were prepared by using natural soy lecithin and a green and organic solvent free method, thus obtaining spherical, small (~ 118 nm), homogeneously dispersed (0.27) and highly negatively charged (~ −62 mV) vesicles. The used amount of oil loaded in liposomes (10, 20, 30 mg/ml) modulated the penetration ability of vesicles in the skin, favoring the deposition of the payload in the deeper strata. The loading in the vesicles potentiated the ability of oil to counteract the damaging effects caused by hydrogen peroxide in keratinocytes and fibroblasts and facilitate their migration in a cell monolayer lesion. Overall findings suggested that the incorporation of lentisk oil in liposomes made from soy lecithin can be an alternative and natural approach to exploit it in pharmaceutical ad cosmetical applications and manufacturing natural products suitable for the treatment of skin lesions.